Harvesting Freedom: The Life of a Migrant Worker in Canada - Allahdua, Gabriel; Dunsworth, Edward (Between the Lines, 2023)
In this singular firsthand account, a former migrant worker reveals a disturbing system of exploitation at the heart of Canada’s farm labour system. When Gabriel Allahdua applied to the Seasonal Agricultural Worker Program in Canada, he thought he would be leaving his home in St. Lucia to work in a country with a sterling human rights reputation and commitment to multiculturalism. Instead, breakneck quotas and a culture of fear dominated his four years in a mega-greenhouse in Ontario. This deeply personal memoir takes readers behind the scenes to see what life is really like for the people who produce Canada’s food. Now, as a leading activist in the migrant justice movement in Canada, Gabriel is fighting back against the Canadian government to demand rights and respect for temporary foreign labourers. Harvesting Freedom shows Canada’s place in the long history of slavery, colonialism, and inequality that has linked the Caribbean to the wider world for half a millennium--but also the tireless determination of Caribbean people to fight for their freedom. -- Publisher's description
Keywords: Agricultural laborers, Foreign; Agricultural laborers, Foreign Canada Biography; Allahdua, Gabriel; Autobiographies; Biographies; Canada; Foreign workers, West Indian; Foreign workers, West Indian Canada History; History

Unpaid Work in Nursing Homes: Flexible Boundaries - Armstrong, Pat (Policy Press, 2023)

Les plateformes de travail numériques: polygraphie d'un nouveau modèle organisationnel - Baril, Émile; Bernier, Jean; Busso, Mariana; Jalette, Patrice; Vultur, Mircea (Collection Sociologie contemporaine, 2023)
Au cours des dix à quinze dernières années, les plateformes de travail numériques se sont fortement développées dans différents secteurs d'activité, comme le transport de personnes et la livraison de repas, ou sous forme d'une multitude de microtâches réalisées en ligne. Des centaines de milliers de travailleurs et travailleuses se retrouvent actuellement dans cette nouvelle gig economy. Quelle est l'importance des plateformes numériques et quelle est leur signification pour le monde du travail ? Menacent-elles de supplanter les relations d'emploi traditionnelles fondées sur des contrats légalement réglementés ? Sont-elles compatibles avec les promesses d'autonomie et de liberté qui constituent leur image de marque ? Quelle est la situation vécue par les travailleurs et les travailleuses des plateformes ? Cet ouvrage tente de répondre à ces interrogations selon une perspective à la fois internationale et multidisciplinaire. Sociologues, économistes et juristes, spécialistes de la question, dressent un portrait saisissant de l'économie des plateformes numériques, analysent les effets de leur développement sur les manières de vivre le travail et soulèvent des nouveaux questionnements et enjeux sociaux pour l'action publique
Keywords: Actes de congrès; Marché du travail Effets des innovations technologiques 2000-...; Organisation du travail Effets des innovations technologiques 2000-...; Travail précaire 2000-...; Uberisation Société; Économie numérique 2000-...

Seeking Social Democracy: Seven Decades in the Fight for Equality - Broadbent, Ed; Abele, Frances; Sas, Jonathan; Savage, Luke (ECW Press, 2023)
The first full-length treatment of Ed Broadbent's ideas and remarkable seven-decade engagement in public life. Ed Broadbent is unique among living political leaders of international stature in offering a fully developed analysis of social democracy and its relevance in the 21st century. His career as a political philosopher, activist, and politician and his conversations with contemporaries such as Willy Brandt, Pierre Elliot Trudeau, Fidel Castro, and Mikhail Gorbachev inform his analysis of the struggles for social justice in the long 20th century. Having come to the socialist and social democratic traditions by way of academic study, Broadbent tested and tempered his ideas in the great postwar struggles over social rights, gender and racial equality, workers' rights, the containment of capital, and reversing the commodification of private life. The book explores the roots of his egalitarianism and the formation of his social democratic ideas, Broadbent's engaged internationalism and relationship with key historical figures, and his experiences and reflections in practical politics and pursuit of government across several of the most momentous decades in the history of Canada. He was a Member of Parliament for over two decades and was, for most of this period, leader of the New Democratic Party. He remains to this day an important social democratic voice in the public debates of the nation. Part political history, part intellectual biography, part manifesto for social democracy this first-ever full-length treatment of Broadbent's thought will be animated in dialogue with three collaborators from different generations, each similarly immersed in the history of social democratic ideas--the result being a fresh analysis of social democracy, Canadian politics, and a lively contribution to current debates and dilemmas. -- Publisher's description
Keywords: Autobiographies; Broadbent, Ed, 1936-; Canada; Canada Politics and government; Canada Politique et gouvernement; Equality; Ottawa authors, musicians, etc; Politics and government; Socialism; autobiographies (literary works)

Lost in Cabbagetown: A Memoir of Surviving Boyhood in 1960s Toronto - Burke, Terry (Dundurn Press, 2023)
A poignant memoir of a rough-and-tumble boyhood on the streets of Toronto's Cabbagetown. When the Burke family left Ireland in 1959, they thought they were leaving the trials and tribulations of the Dublin slums behind. Instead, Molly, Bill, and their nine children found the same poverty and hardship awaiting them in the east end of Toronto. For their sixth-born son, Terry, growing up in Cabbagetown was a daily struggle to survive. Whether it was the bullies on the street or the gangs in Regent Park, fights were an everyday occurrence. School should have been a refuge, but some of the priests and nuns were more terrifying than any street bully. The only escape for Terry was to find his way down into the Don Valley, where he could search the river for muskrat or imagine himself escaping on one of the freight trains, chucking north, up the valley floor. But a childhood in Cabbagetown didn't seem to last very long. Forced into adulthood and driven from home in the wake of tragedy, Terry struggled to survive on his own and find a way back to his family. In this touching memoir, Terry Burke tells a poignant story of hunger, pain, love, and loss, and the enduring bonds of family. --Publisher's description
Keywords: Autobiographies; Autobiography; Biographies; Burke, Terry, 1947- Childhood and youth; Burke, Terry, 1947- Enfance et jeunesse; Cabbagetown (Toronto, Ont.) Biographies; Cabbagetown (Toronto, Ont.) Biography; Ontario Toronto Cabbagetown; autobiographies (literary works)

Feminism's Fight: Challenging Politics and Policies in Canada Since 1970 - Cameron, Barbara; Luxton, Meg (UBC Press, 2023)
Feminism's Fight explores and assesses feminist strategies to advance gender justice through Canadian federal policy from the 1970s to the present. It tells the crucial story of a transformation in how feminism has been treated by governments and asks how new ways of organizing and emerging alliances can advance a feminist agenda of social and economic equality. This timely collection examines the ideas that feminists have put forward in pursuit of the goal of equality and traces the shifting frameworks employed by governments in response. The authors evaluate changing government orientations through the 1970s to 2020, revealing the negative impact on women's lives and the challenges posed for feminists. The COVID-19 pandemic has exacerbated the sexism, misogyny, and related systemic inequalities that remain widespread. Yet it has also revived feminist mobilization and animated calls for a new and comprehensive equality agenda for Canada. Feminism's Fight asks two key questions: What are the lessons from feminist engagement with federal government policy over fifty years? And what kinds of transformative policy demands will achieve the feminist goal of social and economic equality?-- Publisher's description
Keywords: Canada; Feminism Canada History; Femmes Activité politique Canada; Femmes Canada Conditions sociales; Femmes Droit Canada; Femmes Droits Canada; Femmes Politique gouvernementale Canada; Féminisme Canada Histoire; SOCIAL SCIENCE / Women's Studies; Women Canada Social conditions; Women Government policy; Women Government policy Canada; Women Legal status, laws, etc; Women Legal status, laws, etc. Canada; Women Political activity; Women Political activity Canada; Women Social conditions; Women's rights; Women's rights Canada

New Essays in Women's History - Chambers, Lori; Sangster, Joan (Essays in the History of Canadian Law, 2023)
Drawing on engaging case studies, Essays in History of Canadian Law brings the law to life. The contributors to this collection provide rich historical and social context for each case, unravelling the process of legal decision-making and explaining the impact of the law on the people involved in legal disputes. Examining the law not simply as legislation and institutions, but as discourse, practice, symbols, rhetoric, and language, the chapters show the law as both oppressive and constraining and as a point of contention and means of resistance. This collection presents new approaches and concerns, as well as re-examinations of existing themes with new evidence and modes of storytelling. Contributors cover many thematic areas, from criminal to labour, civil, administrative, and human rights law, spanning English and French Canada, and ranging from the mid-eighteenth century to the late twentieth century. The legal cases vary from precedent-setting cases to lesser-known ones, from those driven by one woman’s quest for personal justice to others in which state actors dominate. Bringing to light how the people embroiled in these cases interacted with the legal system, the book reveals the ramifications of a legal system characterized by multiple layers of inequality. -- Publisher's description
Keywords: Canada; Droit Canada Histoire; History; Law; Law Canada History; Women Legal status, laws, etc; Women Legal status, laws, etc. Canada History

United in Action: The History of the Union of Canadian Transportation Employees - Clavette, Ken (Union of Canadian Transportation Employees, 2023)
Despite the centrality of public sector trade unionism in Canada today, its history remains largely unknown. Our attention remains fixed on the classic male proletarians of the industrial revolution. It might surprise you that the history of public sector unionism spans the 20th century, reaching back to the 19th century. United in Action tells the fascinating story of the Union of Canadian Transportation Employees (UCTE), one of five founding components of the Public Service Alliance of Canada (PSAC) in 1966. --Foreword

Enduring Work: Experiences with Canada's Temporary Foreign Worker Program - Connelly, Catherine E. (McGill-Queen's University Press, 2023)
If you believed most of what's said about the Canadian Temporary Foreign Worker program, you might naturally assume that there is a trade-off between workers' poor experiences with the program and employers' significant benefits. In fact, neither is quite true: the experiences of workers are, in reality, far worse than is commonly acknowledged, while employers are not reaping as much benefit as the public might suppose. In Enduring Work Catherine Connelly draws on over one hundred interviews with people connected to different aspects of this program, analyzing their experiences from the perspective of organizational behaviour and human resources management. She compares the lived reality of agricultural workers, in-home caregivers, and low- and high-wage workers, showing how and why each group is vulnerable to mistreatment, albeit in different ways. She further explores how employment agencies and immigration consultants contribute to program abuses. Critically, Enduring Work provides the perspectives of employers, distinguishing between the reluctant users of the program who follow the rules and the reckless users who do not. Groundbreaking in its analysis of an issue very much in the news, Enduring Work unpacks the harms within Canada's Temporary Foreign Worker program and offers nuanced strategies to improve it. -- Publisher's description
Keywords: BUSINESS & ECONOMICS / Labor / General; Canada; Comportement organisationnel Canada; Foreign workers Canada Social conditions; Foreign workers Government policy; Foreign workers Government policy Canada; Foreign workers Social conditions; Organizational behavior; Organizational behavior Canada; Personnel Direction Canada; Personnel management; Personnel management Canada; Programme des travailleurs étrangers temporaires (Canada); Temporary Foreign Workers Program (Canada); Travailleurs étrangers Canada Conditions sociales; Travailleurs étrangers Politique gouvernementale Canada

Defending Animals: Finding Hope on the Front Lines of Animal Protection - Coulter, Kendra (MIT Press, 2023)
An in-depth look at the urgent struggle to protect animals from harm, cruelty, injustice, extinction, and their greatest threat—us. Beloved dogs and cats. Magnificent horses and mountain gorillas. Curious chickens. What do we actually do to protect animals from harm—and is it enough? This engaging book provides a unique and eye-opening exploration of the world of animal protection as people defend diverse animals from injustice and cruelty. From the streets of major US cities to remote farms and tropical forests, Defending Animals is a gritty and moving portrait of the real work of animal protection that takes place in communities, courtrooms, and boardrooms. Globally recognized expert Kendra Coulter takes readers across the different landscapes of animal protection to meet people and animals of all kinds, from cruelty investigators to forensic veterinarians, wildlife rehabilitators and conservation leaders to animal lawyers and entrepreneurs, each working in their own ways to defend animals. Bringing unparalleled research and a distinct and nuanced analytical viewpoint, Defending Animals shows that animal protection is not only physical, intellectual, and emotional work but also a labor so rooted in empathy and care that it just might bridge the vast divide between polarized people and help create a more humane future for us all. -- Publisher's description
Keywords: Animal rights; Animal welfare; Animaux Droits; Bien-être Aspect psychologique; Documents d'information; Human-animal relationships; Informational works; Relations homme-animal; Well-being Psychological aspects

On Class - Dundas, Deborah (Field Notes, 2023)
Deborah Dundas is a journalist who grew up poor and almost didn’t make it to university. In On Class, she talks to writers, activists, those who work with the poor and those who are poor about what happens when we don’t talk about poverty or class—and what will happen when we do. Growing up poor, Deborah Dundas knew what it meant to want, to be hungry, and to long for social and economic dignity; she understood the crushing weight of having nothing much expected of you. But even after overcoming many of the usual barriers faced by lower- and working-class people, she still felt anxious about her place, and even in relatively safe spaces reluctant to broach the subject of class. While new social movements have generated open conversation about gender and racism, discussions of class rarely include the voices of those most deeply affected: the working class and poor. On Class is an exploration of the ways in which we talk about class: of who tells the stories, and who doesn’t, which ones tend to be repeated most often, and why this has to change. It asks the question: What don’t we talk about when we don’t talk about class? And what might happen if, ﬁnally, we did? --Publisher's description

Gigs, Hustles, and Temps: How Precarious Work Lowers Wages, Makes Canadians Poorer and Deprives Workers of Rights- While It Empowers and Enriches Big Corporations - Foster, Jason (Lorimer, 2023)
In this profoundly troubling and incisive look at the state of work and welfare in Canada, Jason Foster reveals the long, often-hidden process that has left our jobs less secure, our livelihoods more uncertain, and the pockets of Canada’s wealthy fatter than ever. This phenomenon, the rise of “precarious work,” touches the entire economy and contributes to levels of income inequality unseen since the early 20th century. Our world is less secure than it has been in generations. Gigs, Hustles, and Temps describes how we got here, and why. Jobs across the economy are increasingly more precarious, and they share similar characteristics: impermanence, little to no benefits, and no union representation. Uber, Starbucks and Amazon have led the way. Governments are contracting out more labour than ever before. Tech companies hire workers on “flexible” contracts without the prospect of long-term employment. Migrant workers, too, are working without a safety net, figuratively and literally. No matter where you fall on the socio-economic ladder, your life is probably more precarious than your parents’ once was. Foster offers insights into the many consequences of our increasingly precarious world. He also details some of the less obvious repercussions of precarious work, including its contribution to the crisis of mental and public health across Canada. Foster argues that the rise of precarious work is more a “return to normal” for capitalist economies. But there is a flip side: advances in worker welfare have come through solidarity, struggle, and negotiation with the forces currently promoting precarious work across Canada's economy. Things don’t have to be the way they are. Gigs, Hustles, and Temps is a comprehensive, accessible, and essential guidebook on the road to a better world. --Publisher's description

Regards croisés sur la grève d'Amoco à Hawkesbury: une histoire ouvrière de l'Ontario français - Gagnon, Andréane (Collection Agora, 2023)
La grève d’Amoco de 1980, lors de laquelle s’est soulevée la population ouvrière de Hawkesbury, marque un temps fort de revendication franco-ontarienne, aujourd’hui pratiquement tombé dans l’oubli. Trois personnes qui ont, chacune à sa façon, pris part à la grève – Serge Denis, politologue, Richard Hudon, animateur social, et Jean Marc Dalpé, dramaturge et écrivain – replongent ici dans leurs souvenirs pour mettre en lumière la conjoncture sociopolitique qui a mené à la mobilisation des travailleurs et travailleuses de la région.Fruit d’un travail de terrain engagé, cet ouvrage, nourri par les témoignages et par de nombreux documents d’archives, démontre que la grève d’Amoco n’était pas une grève comme les autres. Microcosme du contexte sociohistorique dans lequel il s’inscrit, et bien qu’il consiste avant tout en une lutte ouvrière, le mouvement a permis à une communauté minoritaire doublement défavorisée, économiquement et politiquement, de s’affirmer en s’appropriant une nouvelle plateforme pour s’exprimer : le syndicalisme.Les combats de l’Ontario français pour la défense de ses droits se sont depuis déplacés vers les tribunaux, mais cette étude rappelle que sa culture politique s’est d’abord construite dans la rue et qu’il faut, à ce titre, assurer la transmission de ce pan de l’histoire populaire. -- Résumé de l'éditeur
Keywords: 1900-1999; Amoco Fabrics Strike, Hawkesbury, Ont., 1980; Canadiens français Ontario Conditions économiques 20e siècle; Grève de l'Amoco Fabrics, Hawkesbury, Ont., 1980; Grèves et lock-out Textiles et tissus Industrie et commerce Ontario Histoire; Hawkesbury (Ont.) Histoire 20e siècle; History; Labor disputes; Labor disputes Ontario Hawkesbury History; Ontario; Ontario Hawkesbury; Strikes and lockouts Textile industry; Strikes and lockouts Textile industry Ontario History; Textile workers Labor unions; Textile workers Labor unions Ontario History 20th century; Travail Conflits Ontario Hawkesbury Histoire; Travailleurs du textile Syndicats Ontario Histoire 20e siècle

Essential Work, Disposable Workers: Migration, Capitalism, and Class - Henaway, Mostafa (Fernwood Publishing, 2023)
Recent years have seen massive waves of migration from the Middle East, Latin America, and Africa to Europe and North America and a corresponding rise in anti-immigrant, far-right populism in host countries, placing the question of migration at the forefront of politics and social movements. Henaway seeks to understand these patterns through contextualizing global migration within a history of global capitalism, class formation, and the financialization of migration. As globalization intensifies, a neoliberal labour market forces workers around an unevenly developed world to compete for wages--not through foreign investment and outsourcing, but through an increasingly mobile working class. Henaway rejects the right-wing response of restricting or "managing" immigration through temporary worker programs and instead suggests that stopping a race to the bottom for all working people involves building solidarity with the struggles of these migrants for decent work and justice. Through examining the organizing strategies of migrant workers at giants like Amazon and Wal-Mart as well as discount retailers like Dollarama and Sports Direct, the immense power and agency of precarious workers in global companies like UBER or Airbnb, the successful resistance of taxi drivers or fast food workers around the world, and the contemporary mass labour movement organized by new unions and workers' centres, Henaway shows how migrant demands and strategies can help shape radical working class politics in North America and Europe. --Publisher's description
Keywords: Globalization; Labor movement; Migrant labor; Precarious employment; SOCIAL SCIENCE / Emigration & Immigration; Social classes

Gin, Turpentine, Pennyroyal, Rue - Higdon, Christine (ECW Press, 2023)
Four working-class Vancouver sisters, still reeling from the impact of World War I and the pandemic that stole their only brother, are scraping by but attempting to make the most of the exciting 1920s. Gin, Turpentine, Pennyroyal, Rue is a love story — but like all love stories, it’s complicated … Morag is pregnant; she loves her husband. Georgina can’t bear hers and dreams of getting an education. Harriet-Jean, still at home with her opium-addicted mother, is in love with a woman. Isla’s pregnant too — and in love with her sister’s husband. Only one soul knows about Isla’s pregnancy, and it isn’t the father. When Isla resorts to a back-street abortion and nearly dies, Llewellyn becomes hellbent on revenge. But can revenge lead to anything but disaster for a man like Llew — a policeman tangled up in running rum to Prohibition America? Gin, Turpentine, Pennyroyal, Rue is immersed in the complex political and social realities of the 1920s and, not-so ironically, of the 2020s: love, sex, desire, police corruption, abortion, addiction, and women wanting more. Beautifully written, with a loveable cast of characters, this novel is a tender account of love that cannot be acknowledged, of loss and regret, risk and defiance, abiding friendship, and the powerful bonds of chosen family. --Publisher's description

Tipping Point for Advanced Capitalism: Class, Class Consciousness and Activism in the “Knowledge Economy” - Livingstone, D. W. (David W.) (Fernwood Publishing, 2023)
The aim: to rejuvenate study and understanding of class relations in advanced capitalism. The book is an original synthesis of theorizing about class grounded in the production process, revealing a distinct tripartite class structure of owners, managers and non-managerial workers. Changes since the 1980s are traced and significant increases of non-managerial professional employees and middle managers are documented beyond any prior empirical research. Higher levels of oppositional and revolutionary class consciousness are conceptualized in terms of support for rights of capital and labour, and the extent of their expression in employed labour forces is estimated in terms only previously attempted briefly in the wake of 1960s protest movements. Connections between objective class positions and levels of class consciousness are analyzed in unprecedented depth; the solidary hegemonic consciousness of corporate capitalists, declining pro-capital oppositional consciousness among other employers and upper managers, and the pro-labour oppositional consciousness of pluralities of non-managerial workers (including professional employees) are all documented more fully than in prior studies. Strategic connections between class, class consciousness and issues of poverty and global warming are identified. Contending class forces’ engagement in actions toward an imminent system tipping point are uniquely traced. Main sources of evidence are all the national surveys in G7 and Nordic countries in the 1980s that provide relevant data, and the author’s unique Canadian national surveys in 2004, 2010 and 2016, supplemented by interviews with class leaders. A website encourages further class-based studies of advanced capitalism with similar measures to aid ecological sustainability and economic democracy. --Publisher's description (WorldCat record)
Keywords: Capitalism; Class consciousness; Knowledge economy; Social classes

Brightening My Corner: A Memoir of Dreams Fulfilled - Malloy, Ruth Lor (Barclay Press, 2023)
Ruth Lor started life Chinese in a small Canadian town. Driven by curiosity, a yen for adventure, and a wish to be useful, she managed to spend her life fighting racial discrimination. In Washington, D.C., she fought segregation by sitting in at "whites only" restaurants and swimming in "whites only" pools. She planted trees in Mexico, painted houses for Inuit victims of tuberculosis in the Canadian Arctic, and helped distribute food to refugees in Taiwan. When China reopened to foreigners after its Cultural Revolution, Ruth wrote the first English-language guidebook about that enormous country.Ruth covered the war in Vietnam, crossed Himalayan passes on foot and horseback, and faced down an angry elephant in Africa. She worked in India to reduce prejudice against that country's caste of transgender hijras. She and her husband housed refugees in their Maryland home after the Vietnam War ended.Now in her nineties, Ruth still works with refugees, and she still brightens her corner of the world, wherever she is. --Publisher's description

Cleaning Up: Portuguese Women's Fight for Labour Rights in Toronto - Miranda, Susana P.; Iacovetta, Franca (Between the Lines, 2023)
This fascinating book uncovers the little-known, surprisingly radical history of the Portuguese immigrant women who worked as night-time office cleaners and daytime “cleaning ladies” in postwar Toronto. Drawing on union records, newspapers, and interviews, feminist labour historians Susana P. Miranda and Franca Iacovetta piece together the lives of immigrant women who bucked convention by reshaping domestic labour and by leading union drives, striking for workers’ rights, and taking on corporate capital in the heart of Toronto’s financial district. Despite being sidelined within the labour movement and subjected to harsh working conditions in the commercial cleaning industry, the women forged critical alliances with local activists to shape picket-line culture and make an indelible mark on their communities. Richly detailed and engagingly written, Cleaning Up is an archival treasure about an undersung piece of working-class history in urban North America. --Publisher's description

From Consent to Coercion: The Continuing Assault on Labour - Panitch, Leo; Evans, Bryan M.; Fanelli, Carlo; Swartz, Donald; Gindin, Sam (University of Toronto Press, 2023)
From Consent to Coercion examines the increasing assault against trade union rights and freedoms in Canada by federal and provincial governments. Centring the struggles of Canadian unionized workers, this book explores the diminution of the welfare state and the impacts that this erosion has had on broader working-class rights and standards of living. The fourth edition witnesses the passing of an era of free collective bargaining in Canada--an era in which the state and capital relied on obtaining the consent of workers and unions to act as subordinates in Canada's capitalist democracy. It looks at how the last twenty years have marked a return to a more open reliance of the state and capital on coercion--on force and on fear--to secure that subordination. From Consent to Coercion considers this conjuncture in the Canadian political economy amid growing precarity, poverty, and polarization in an otherwise indeterminate period of austerity. This important edition calls attention to the urgent task of rebuilding and renewing socialist politics--of thinking ambitiously and meeting new challenges with unique solutions to the left of social democracy. -- Publisher's description
Keywords: Canada; Collective bargaining; Collective bargaining Canada History; History; Labor unions; Labor unions Canada History; Labor unions Law and legislation; Labor unions Law and legislation Canada History

Travailler moins ne suffit pas (Collection Polémos, 2023)
« Est-ce qu’il suffit de travailler moins pour retrouver l’équilibre entre les différentes facettes de nos vies surchargées ? La réduction du temps de travail est une revendication de longue date pour améliorer notre qualité de vie. En passant moins de temps au travail, nous pourrions enfin reprendre notre souffle et consacrer plus de temps à nos relations sociales, aux tâches domestiques ou encore pour s’engager dans la communauté. Mais est-ce que notre travail nous comble et contribue au bien commun ? Julia Posca interroge notre rapport au travail, explore sa nature et envisage les voies à emprunter pour lui redonner un sens. À la dystopie dans laquelle nous nous enfonçons toujours un peu plus, nous pourrions opposer l’utopie du travail « démarchandisé, démocratisé et dépollué ». Une invitation à revoir l’organisation du travail pour qu’il réponde d’abord aux besoins les plus « authentiques » : assurer à tous et toutes une existence digne, entretenir des relations riches, léguer une vie bonne aux futures générations. »--Quatrième de couverture
Keywords: Hours of labor; Industrial sociology; Methods engineering; Organisation du travail; Réduction du temps de travail; Sociologie industrielle; Syndicalism; Syndicalisme; Travail Aspect psychologique; Work Psychological aspects

Countercurrents: Women's Movements in Postwar Montreal - Ricci, Amanda (Studies on the history of Quebec, 2023)
In the decades following the Second World War, women from all walks of life became increasingly frustrated by the world around them. Drawing on long-standing political traditions, these women bound together to revolutionize social norms and contest gender inequality. In Montreal, women activists inspired by Red power, Black Power, and Quebec liberation, among other social movements, mounted a multifront campaign against social injustice. Countercurrents looks beyond the defining "waves" metaphor to write a new history of feminism that incorporates parallel social movements into the overarching narrative of the women's movement. Case studies compare and reflect on the histories of the Quebec Native Women's Association, the Congress of Black Women, the Front de libération des femmes du Québec, various Haitian women's organizations, and the Collectif des femmes immigrantes du Québec and the political work they did. Bringing to light previously overlooked archival and oral sources, Amanda Ricci introduces a new cast of characters to the history of feminism in Quebec. The book presents a unique portrait of the resurgence of feminist activism, demonstrating its deep roots in Indigenous and Black communities and a transnational scope with wide-ranging inspirations and preoccupations. Advancing cross-cultural perspectives on women's movements, Countercurrents looks to the history of women's activism in Montreal and finds new ways of defining feminist priorities and imagining feminist futures. -- Publisher's description
Keywords: 1900-1999; Feminism; Feminism Québec (Province) Montréal History 20th century; Femmes Activité politique Québec (Province) Montréal Histoire 20e siècle; Féminisme Québec (Province) Montréal Histoire 20e siècle; History; Mouvements sociaux Québec (Province) Montréal Histoire 20e siècle; Québec Montréal; SOCIAL SCIENCE / Women's Studies; Social movements; Social movements Québec (Province) Montréal History 20th century; Women Political activity; Women Political activity Québec (Province) Montréal History 20th century

Building a Better World: An Introduction to the Labour Movement in Canada - Ross, Stephanie; Savage, Larry (Fernwood Publishing, 2023)
This fourth edition...offers a comprehensive introductory overview of Canada’s labour movement. The book explores why workers form unions; assesses their organization and democratic potential; examines issues related to collective bargaining, grievances and strike activity; charts the historical development of labour unions; and describes the gains unions have achieved for their members and all working people. This new and expanded edition also analyzes the challenges facing today’s labour movement as a result of COVID-19 and the strategies being developed to overcome them. --Publisher's description
Keywords: Canada; Labor movement; Labor movement Canada; Labor unions; Labor unions Canada; Mouvement ouvrier Canada; Syndicats Canada

Forgiveness - Sakamoto, Mark (Playwrights Canada Press, 2023)
Mitsue Sakamoto and Ralph MacLean have both suffered tremendous loss during WWII: Mitsue as a survivor of a Japanese Canadian internment camp, and Ralph as a prisoner in a Japanese POW camp. In order to rebuild their lives and their families after the war, Ralph and Mitsue must find the grace and generosity necessary to forgive those who have wronged them. Their paths eventually cross in 1968 when Mitsue's son and Ralph's daughter begin dating, and Ralph is invited to Mitsue's home for dinner.This soaring adaptation of Mark Sakamoto's award-winning memoir affirms the power of forgiveness and shows us that in our challenging times characterized by political divisiveness, xenophobia, and race hatred, the story of Mitsue and Ralph's personal triumphs over hatred, injustice, violence, and bigotry remains vitally relevant and urgently necessary. -- Publisher's Description
Keywords: 1939-1945; Adaptations scéniques; Biographical drama; Canada; Canadiens d'origine japonaise Relogement et internement forcés, 1941-1949 Théâtre; Canadiens d'origine japonaise Théâtre; Drama; Families; Guerre mondiale, 1939-1945 Prisonniers et prisons des japonais Théâtre; Historical drama; Japan; Japanese Canada Drama; Japanese Canada Forced removal and internment, 1942-1945 Drama; Japanese Canadians Drama; Japanese Canadians Forced relocation and internment, 1941-1949 Drama; MacLean, Ralph, 1922- Famille Théâtre; MacLean, Ralph, 1922- Family Drama; Prisoners of war; Prisoners of war Canada Drama; Prisoners of war Japan Drama; Prisonniers de guerre Canada Théâtre; Prisonniers de guerre Japon Théâtre; Sakamoto, Mark, 1977- Famille Théâtre; Sakamoto, Mark, 1977- Family Drama; Sakamoto, Mitsue, 1920- Famille Théâtre; Sakamoto, Mitsue, 1920- Family Drama; Theatrical adaptations; Théâtre; Théâtre biographique; Théâtre historique; World War, 1939-1945 Prisoners and prisons, Japanese Drama

Conscripted to Care: Women on the Frontlines of the COVID-19 Response - Smith, Julia (McGill-Queen's University Press, 2023)
With the vast majority of healthcare and social workers identifying as women, the vanguard of the COVID-19 response was distinctly gendered. In Conscripted to Care, Julia Smith introduces us to the women who faced the worst effects of the pandemic and the inequities it exposed. Through clear prose and fascinating critical analysis, she documents their largely unseen contributions and sacrifices, both professionally and domestically. Drawing on interviews and focus groups with nearly 200 women from a range of backgrounds and occupations, Smith reveals how structural inequality put women on the frontlines of the pandemic response, yet with inadequate resources and little voice in decision-making. Women not only shouldered the triple burden of paid work, unpaid care, and mental load, but also increased emotional labour. While some women were categorized as "essential," others remained in the shadows--all faced unsustainable workloads, moral distress, and burnout, while continuing to demand better services for those in their care. An analysis of Canada's COVID-19 response from the perspective of those who staffed it, Conscripted to Care presents crucial lessons for those interested in public health and how it relates to gender and economic equality, as well as public policy. -- Publisher's description
Keywords: Aidantes naturelles Canada; COVID-19 Pandemic, 2020-2023 Social aspects Canada; Canada; Equality Health aspects; Equality Health aspects Canada; Femmes Canada Conditions sociales 21e siècle; Femmes Canada Conditions économiques 21e siècle; Medical personnel Canada; Pandémie de COVID-19, 2020-2023 Aspect social Canada; Personnel féminin Canada Conditions sociales 21e siècle; Personnel féminin Canada Conditions économiques 21e siècle; Personnel médical Canada; Public health; Public health Canada; Santé publique Canada; Since 2000; Social aspects; Women Canada Economic conditions 21st century; Women Canada Social conditions 21st century; Women Economic conditions; Women Social conditions; Women caregivers Canada; Women employees Canada Economic conditions 21st century; Women employees Canada Social conditions 21st century; Women employees Economic conditions; Women employees Social conditions; Égalité (Sociologie) Aspect sanitaire Canada

Care Activism: Migrant Domestic Workers, Movement-Building, and Communities of Care - Tungohan, Ethel (NWSA / UIP First Book Prize Series, 2023)
Care activism challenges the stereotype of downtrodden migrant caregivers by showing that care workers have distinct ways of caring for themselves, for each other, and for the larger transnational community of care workers and their families. Ethel Tungohan illuminates how the goals and desires of migrant care worker activists goes beyond political considerations like policy changes and overturning power structures. Through practices of subversive friendships and being there for each other, care activism acts as an extension of the daily work that caregivers do, oftentimes also instilling practices of resistance and critical hope among care workers. At the same time, the communities created by care activism help migrant caregivers survive and even thrive in the face of arduous working and living conditions and the pains surrounding family separation. As Tungohan shows, care activism also unifies caregivers to resist society's legal and economic devaluations of care and domestic work by reaffirming a belief that they, and what they do, are important and necessary. --Publisher's description

Transnational Employment Strain in a Global Health Pandemic: Migrant Farmworkers in Canada - Vosko, Leah F.; Basok, Tanya; Spring, Cynthia (Palgrave pivot, 2023)
The 2020-22 COVID-19 pandemic reinforced inequalities between the global North and South, amplifying pre-existing disparities between migrant and citizen/permanent resident workers in receiving and sending states worldwide. In contexts such as Canada, it also underscored that many workers in occupations and sectors deemed “essential” enough to be exempt from stay-at-home orders and other public safety measures are migrants, a sizeable number of whom sustain Canada’s food supply through their work in its agricultural industry. This book explores the dynamics behind the pandemic’s deleterious outcomes for this vital group of workers, highlighting migrant farmworkers importance to the Canadian economy, society, and the world of work alongside the conditions they endured before and during the global health pandemic through policy and media analysis and open-ended interviews with workers enrolled in two streams of Canada’s Temporary Foreign Worker Program (TFWP) as well as migrants without legal status employed in agriculture located in Ontario and Quebec. Advancing the notion of transnational employment strain, the authors derive insight from the employment strain model, a framework for understanding risks to the physical and psychological well-being of workers, and expand it to account for migrants’ relationships across transnational space. --Publisher's description
Keywords: COVID-19 Pandemic, 2020-2023 Economic aspects Canada; Canada; Economics; Influence (Literary, artistic, etc.); Migrant agricultural laborers; Migrant agricultural laborers Canada; Migrant agricultural laborers Government policy; Migrant agricultural laborers Government policy Canada; Pandémie de COVID-19, 2020-2023 Aspect économique Canada; Since 2020; Travailleurs agricoles migrants Canada; Travailleurs agricoles migrants Politique gouvernementale Canada

Denison Avenue - Wong, Christina (ECW Press, 2023)
Bringing together ink artwork and fiction, Denison Avenue by Daniel Innes (illustrations) and Christina Wong (text) follows the elderly Wong Cho Sum, who, living in Toronto’s gentrifying Chinatown–Kensington Market, begins to collect bottles and cans after the sudden loss of her husband as a way to fill her days and keep grief and loneliness at bay. In her long walks around the city, Cho Sum meets new friends, confronts classism and racism, and learns how to build a life as a widow in a neighborhood that is being destroyed and rebuilt, leaving elders like her behind. A poignant meditation on loss, aging, gentrification, and the barriers that Chinese Canadian seniors experience in big cities, Denison Avenue beautifully combines visual art, fiction, and the endangered Toisan dialect to create a book that is truly unforgettable. --Publisher's description